Building Health Care System Capacity: Training Health Care Professionals in Disaster Preparedness Health Care Coalitions. Issue 2 (6th February 2015) - Walsh, Lauren; Craddock, Hillary; Gulley, Kelly; Strauss-Riggs, Kandra; Schor, Kenneth W.
Abstract: Introduction: This study aimed to learn from the experiences of well-established, disaster preparedness-focused health care coalition (HCC) leaders for the purpose of identifying opportunities for improved delivery of disaster-health principles to health professionals involved in HCCs. This report describes current HCC education and training needs, challenges, and promising practices. Methods: A semi-structured interview was conducted with a sample of leaders of nine preparedness-focused HCCs identified through a 3-stage purposive strategy. Transcripts were analyzed qualitatively. Results: Training needs included: stakeholder engagement; economic sustainability; communication; coroner and mortuary services; chemical, biological, radiological, nuclear, and explosives (CBRNE); mass-casualty incidents; and exercise design. Of these identified training needs, stakeholder engagement, economic sustainability, and exercise design were relevant to leaders within HCCs, as opposed to general HCC membership. Challenges to education and training included a lack of time, little-to-no staff devoted to training, and difficulty getting coalition members to prioritize training. Promising practices to these challenges are also presented. Conclusions: The success of mature coalitions in improving situational awareness, promoting planning, and enabling staff- and resource-sharing suggest the strengths and opportunities that are inherent within these organizations. However, offering effective education and training opportunities is a challenge in the absence of ubiquitous support, incentives, or requirements among health care professions. Notably, an online resource repository would help reduce the burden on individual coalitions by eliminating the need to continually develop learning opportunities. L Walsh, H Craddock, K Gulley, K Strauss-Riggs, KW Schor .Building health care system capacity: training health care professionals in disaster preparedness health care coalitions .Prehosp Disaster Med .2015 ;30 (2 ):1 -8 .